P. Ramlee, erti yang sakti / : Ahmad Sarji.. - A. H. Ahmad Sarji (Subang Jaya, Selangor Darul Ehsan, Malaysia: Pelanduk Publications, 1999)
On P. Ramlee, Malaysian film star.
Keywords: P. Ramlee, -- 1928-1973.; Actors -- -- Malaysia